Efficacy and Safety of Percutaneous Cystolithalopexy in Children Under 5 Years of Age - Tariq Ahmad, Farman Ullah Khan, Sajjad Ali, Muhammad Asif Ammar (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To assess the efficacy and safety of percutaneous cystolithalopexy in children under 5 years of age Study design: Retrospective study Place: Department of Paediatric Urology Institute of Kidney Diseases Hayat Abad Peshawar Methodology: Retrospective descriptive study was conducted in Institute of kidney diseases Peshawar between Jan 2020 and January 2022. After applying the inclusion and exclusion criteria all patients in the mentioned period were include in his study. Results were inferred as frequency and percentages. Results: Without observing any difference for age and gender 100% clearance was achieved in all patients with the most prominent complication being supra pubic catheter leakage which was treated conservatively. Conclusions: Percutaneous cystolithalopexy is safe and efficient for the management of bladder stone under 5 years Keywords: Bladder Calculi, Percutaneous Cystolithalopexy, Urolithiasis, Lithiasis